Pengaruh Harga Sewa, Fasilitas, Dan Kualitas Pelayanan Terhadap Kepuasan Tenant Di The Plaza Millennium. - Haikal, Muhammad; Prayogo, Rangga Restu (Pascasarjana STIE Amkop Makassar, 2025)
This study aims to determine the influence of Price, Facilities and Service Quality on Tenant Satisfaction at The Plaza Millennium. The type of research used is descriptive quantitative research with a sampling technique, namely non-probability. The population used in this study is consumers of The Plaza Millennium tenants and uses a sample of 177 samples with the technique of determining saturated samples. The data processing in this study uses Smart PLS software version 4. Based on the results of the study, it was obtained that the rental price variable had a positive effect on Consumer Satisfaction, the Facility variable did not have a positive effect on Consumer Satisfaction, and the Service Quality variable had a positive effect on Consumer Satisfaction. Then the variables of Rental Price, Facilities and Service Quality have a positive and significant effect on the Consumer Satisfaction variable. Keyword : Price, Facilities, Service Quality and Consumer Satisfaction